Architecture and differential hydrocarbon enrichment of basins under joint constraints of basement nature and regional stresses: A case study of the passive continental margin basins along the East Coast of Canada - Zhenrui Bai; Naxin Tian; Gaokui Wu; Yanyang Wang; Kun Tian (Petroleum)
The East Coast of Canada presents multiple passive continental margin basins (PCMBs) characterized by significant architectural differences and limited oil and gas discoveries, establishing these basins as the global frontier for hydrocarbon exploration. Limited understanding of the characteristics of basin architectures and their control of hydrocarbon accumulation hinders exploration breakthroughs in these basins. Using magnetic anomaly, seismic, and drilling data, this study conducts integrated geological and geophysical interpretations of the PCMBs. Accordingly, this study reveals that the PCMBs have undergone three evolutionary stages, namely rifting (comprising three episodes), depression, and continental margin, with the synthem of each stage being referred to as rift layer, depression layer, and continental margin layer, respectively. Under the control of transform faults and basement nature, four distinct types of PCMBs have formed: transtensional, transform, gentle-rampy, and volcanic rifted types from south to north. The basins with varying architectures govern the sedimentary filling, the combination of petroleum system elements, and differential hydrocarbon accumulation across three major types of synthems. Furthermore, this study highlights substantial hydrocarbon exploration potentials in the turbidite sandstones within the slope and basin-floor areas of the transtensional and transform types of PCMBs, as well as in the deltaic sandstones within the rift and depression layers of the gentle-rampy type of PCMBs.